Lecturers’ Job Effectiveness through the Use of E-Learning Facilities in University of Ibadan - Sunday Nnamdi Okocha (African Journal of Behavioural and Scale Development Research, 2021)
The use of e-learning facilities is expected to foster lecturers' job effectiveness in higher institutions. However, observation revealed that challenges like ease of use and technical know-how persist. This study, investigated lecturers' job effectiveness through the use of e-learning facilities in the University of Ibadan. Two research questions were raised. The study adopted non-experimental design. Population comprised 926 lecturers in faculties, institutes and centres in the University of Ibadan. Fourteen faculties (48 departments), 3 institutes and 2 centres which are academic units domiciled in the University main campus were purposively selected due to proximity. Five lecturers were randomly selected from each academic unit, giving a total sample of 265 lecturers. Data was collected using Lecturers' Job Effectiveness Questionnaire (LJEQ) validated through content validity with ordinal alpha reliability of r=0.95. Analysis was carried out using frequency and unpaired t-test. Results showed that lecturers recognised that the use of e-learning facilities could enhance their job effectiveness. However, majority of them do not often use electronic board. Further, result showed that lecturers' gender use of e-learning facilities and job effectiveness in the University of Ibadan was not significant. The study, recommends that lecturers should use e-learning facilities for increased productivity in carrying out their academic work.